Identifying long-term stable refugia for relict plant species in East Asia. Issue 1 (December 2018) - Tang, Cindy; Matsui, Tetsuya; Ohashi, Haruka; Dong, Yi-Fei; Momohara, Arata; Herrando-Moraira, Sonia; Qian, Shenhua; Yang, Yongchuan; Ohsawa, Masahiko; Luu, Hong; Grote, Paul; Krestov, Pavel; et al.
Abstract Today East Asia harbors many "relict" plant species whose ranges were much larger during the Paleogene-Neogene and earlier. The ecological and climatic conditions suitable for these relict species have not been identified. Here, we map the abundance and distribution patterns of relict species, showing high abundance in the humid subtropical/warm-temperate forest regions. We further use Ecological Niche Modeling to show that these patterns align with maps of climate refugia, and we predict species' chances of persistence given the future climatic changes expected for East Asia. By 2070, potentially suitable areas with high richness of relict species will decrease, although the areas as a whole will probably expand. We identify areas in southwestern China and northern Vietnam as long-term climatically stable refugia likely to preserve ancient lineages, highlighting areas that could be prioritized for conservation of such species. East Asia contains "relict" plant species that persist under narrow climatic conditions after once having wider distributions. Here, using distribution records coupled with ecological niche models, the authors identify long-term stable refugia possessing past, current and future climatic suitability favoring ancient plant lineages.